Use of Iron Sucrose Complex in Treatment of Anemia in Pregnancy (Bangladesh Journal of Obstetrics & Gynaecology, 2013)
Objective: To demonstrate the value of iron sucrose complex in the treatment of anemia in  pregnancy.Methods: It is a prospective clinical study, of 35 consecutive pregnant women suffering from  anemia in pregnancy. The study was conducted over a period of twelve months. Hemoglobin  concentration was measured three times during pregnancy. All women consumed timed release iron from 17 weeks onward up to birth of the baby. If hemoglobin level is (8.5 - 9) gm/dl, parentral Iron sucrose complex 2 doses (400gm of iron) were given intravenously and hemoglobin  level was checked after 15 days.Results: There were 35 women who completed the treatment and data was available for  analysis. Their mean age was 27.5(range21-35) years. Fifty six percent were 2nd gravid. Twenty eight (28%) percent women in 1st half of pregnancy, 53% in 2nd trimester and 16% in 3rd trimester suffering from moderate anemia and treated with iron sucrose complex (ISC). The average Hemoglobin concentration before treatment was 8.47gm/dl and after treatment  was 9.67gm/dl. There was a statistically significant improvement in hemoglobin concentration. Three women developed side effects and did not get 2nd dose.Conclusion: Intravenous iron therapy is safe, convenient and effective in treatment of iron  deficiency anemia during pregnancy. The intravenous iron therapy can replace blood transfusion in antenatal period in many patients. DOI: http://dx.doi.org/10.3329/bjog.v25i1.13728 Bangladesh J Obstet Gynaecol, 2010; Vol. 25(1) : 20-23